Triglyceride-Glucose Index as a Biochemical Predictor of Hypertension in Patients with Type 2 Diabetes and Prediabetes: Evidence from the NHANES Database: TyG Index and Hypertension in Diabetes/Prediabetes - Dai, Tianyu; Wang, Fangze; Deng, Hanqing; Li, Muyuan; Zhang, Jihu; Wang, Jian (Journal of Medical Biochemistry, 2025)
Background: The triglyceride-glucose (TyG) index, derived from fasting triglyceride and glucose levels, has emerged as a reliable biochemical marker of insulin resistance. However, its relationship with hypertension (HTN) in diabetic and prediabetic populations remains insufficiently studied.Methods: Using data from 2,440 adults in the U.S. National Health and Nutrition Examination Survey (NHANES, 2011–2018), we investigated the association between the TyG index and HTN. Biochemical assays included enzymatic measurement of serum triglycerides (Beckman Coulter DxC800) and plasma glucose (hexokinase-based methods on Roche Cobas systems), from which the TyG index and related indices (TyG-BMI, TyG-WC, TyG-WHtR) were calculated. Logistic regression models adjusted for demographic, anthropometric, and biochemical covariates were used to estimate odds ratios (OR) for HTN risk.Results: Participants with HTN exhibited significantly higher TyG index levels compared with non-hypertensives (8.44 vs. 8.38, P
Keywords: Triglyceride-glucose index; biochemical marker; hypertension; type 2 diabetes; NHANES